RELATIONSHIP BETWEEN EDUCATION, KNOWLEDGE, AND MOTHER'S DIET WITH THE STATUS AND NUTRITION ADEQUACY OF INFANTS AGED 0-6 MONTHS AT THE HADIJAH PRIMARY OUTPATIENT CLINIC - Wismaria Putri Carolina Zai; Fidia Wulan Safitri Tambunan; Lince Yunika; Luthfia Thahira; Maiya Maulani; Tiarnida Nababan (PT. Radja Intercontinental Publishing, 2025)
Nutritional status is an event that describes the health of a baby and is the result of the interaction between the food consumed and its use by the body. Parental education is one of the factors for the success of providing Exclusive Breastfeeding. However, knowledge can also influence the success of Exclusive Breastfeeding. While the mother's diet affects the nutritional status of her baby. The purpose of this study was to determine whether there is a Relationship between Education, Knowledge, and Mother's Diet with the Status and Nutritional Adequacy of Infants 0-6 Months at the Hadijah Outpatient Clinic 2024. This type of research is Quantitative research with analytical surveys. The design of this study uses Cross Sectional. The population in this study were mothers who had babies aged 0-6 months as many as 80 respondents. The sampling technique was Simple Random Sampling consisting of 67 respondents. Data collection techniques using questionnaires and observations. Data analysis using Chi-Square. The results of this study were mothers who had high school education as many as 49 people (73.1%), and mothers who had junior high school education as many as 1 person (1.5%). Mothers who have high knowledge are 49 people (73.1%), and low knowledge is 7 people (10.4%). Mothers who have good eating patterns are 33 people (49.3%) and mothers who have poor eating patterns are 12 people (17.9%). The conclusion of this study shows that there is no relationship between education and the status and nutritional adequacy of infants 0-6 months, but there is a relationship between knowledge and eating patterns with the status and nutritional adequacy of infants 0-6 months.